Restorative Justice as a Means to Effective Crime Control and Alternative to Imprisonment. Conflict as Property Revisited - Płatek, Monika (Sociologija. Mintis ir veiksmas, 2007)
The article presents the route of restorative justice in Poland – from the very idea towards its implementation in criminal law, criminal procedures, and also as an alternative for imprisonment. It discusses the processes of the development of mediation institute and other forms of restorative justice in Poland, emphasizing the problems that have been faced and the ways to overcome those difficulties. It also stresses the possible dangers that, the author argues, we are not willing to see yet. Perceiving a crime as a conflict, and conflict as property that should belong to parties involved in it, the author points out to the danger within benign developments of rational policy, which might also lead to stealing the conflict from those it belongs to. Voting for more severe punishment and, thus, using victims as a pretext for making criminal law to serve political interests – is one of the identified risks. So the article, on one side, highlights the importance to keep restorative idea and practice as a tool to help the victims to regain their voices, and on the other – to be able to see a human being in a person who committed an offence. Other important agents in the mediation process are mediators. They should also be aware of the dangers and do everything to prevent themselves from stealing the conflict and act like those who share the space and life in Vidaråsen. Thus, Conflict as property will be just like a warning for us to leave the room for victim’s and other party’s wants and needs.